1997
DOI: 10.1046/j.1365-2958.1997.5391899.x
|View full text |Cite
|
Sign up to set email alerts
|

SpsA, a novel pneumococcal surface protein with specific binding to secretory Immunoglobulin A and secretory component

Abstract: SummaryThe interaction of pathogenic bacteria with host serum and matrix proteins is a common strategy to enhance their virulence. Streptococcus pneumoniae colonizes the human upper respiratory tract in healthy individuals and is also able to cause invasive diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
294
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(307 citation statements)
references
References 66 publications
9
294
0
4
Order By: Relevance
“…This also implies that the heterologously expressed PspC is functional in other Grampositive bacteria and no significant difference in growth rates was observed between lactococci expressing or lacking PspC. Several studies have reported the necessity of a PspC-hpIgR interaction for pneumococcal adhesion to and internalization by host epithelial cells Bergmann & Hammerschmidt, 2006;Hammerschmidt et al, 1997Hammerschmidt et al, , 2007.…”
Section: Discussionmentioning
confidence: 86%
“…This also implies that the heterologously expressed PspC is functional in other Grampositive bacteria and no significant difference in growth rates was observed between lactococci expressing or lacking PspC. Several studies have reported the necessity of a PspC-hpIgR interaction for pneumococcal adhesion to and internalization by host epithelial cells Bergmann & Hammerschmidt, 2006;Hammerschmidt et al, 1997Hammerschmidt et al, , 2007.…”
Section: Discussionmentioning
confidence: 86%
“…PIgR also binds to bacterial components such as Streptococcus pneumonia-derived SpsA protein (59,60). FSC can bind to SpsA and prevent invasion of respiratory epithelial cells by S. pneumonia.…”
Section: Biological Functions Of Pigrmentioning
confidence: 99%
“…CbpA is an important pneumococcal virulence factor associated with nasopharyngeal colonization, adherence of pneumococci to epithelial cells, and the ability of the pathogen to cause lung infection (27,28). It binds the secretory component of sIgA, and also inhibits complement activation by binding C3 and factor H (29)(30)(31). CbpA is also a protective immunogen in mice and has been proposed as a component of protein-based pneumococcal vaccines for use in humans (32).…”
Section: Effect Of Hk06 and Rr06 Deletion On Pneumococcal Virulence Pmentioning
confidence: 99%